2021
DOI: 10.3390/nu13124193
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Changes and Anxiety during the Coronavirus Pandemic: Differences between the Sexes

Abstract: The SARS-CoV-2 (COVID-19) pandemic has been associated with both increased anxiety, deterioration in diet and weight gain. These associations may differ by sex. The present report examines differences by sex in diet quality in order to determine whether associations between diet and psychological stress during the initial phase of the COVID-19 pandemic differed by sex. This online study is available internationally in seven languages. The Mediterranean Diet Score was used to measure diet quality, while the Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…The remaining 18 studies were cross-sectional, including one study conducted among children which reported a statistically significant inverse association between dairy consumption and anxiety; i.e., more dairy intake was associated with lower risk of anxiety [ 107 ]. Among the 17 cross-sectional studies of adult populations, 4 reported a statistically significant inverse association [ 5 , 13 , 110 , 111 ], 11 showed no association [ 6 , 7 , 14 , 16 , 57 , 60 , 106 , 112 115 ], and 2 noted mixed associations [ 12 , 104 ]. One study noted a statistically significant inverse association for women, but no association for men [ 12 ], while another study indicated a statistically significant inverse association for low-fat dairy intake and a positive association for high-fat dairy consumption [ 104 ].…”
Section: Resultsmentioning
confidence: 99%
“…The remaining 18 studies were cross-sectional, including one study conducted among children which reported a statistically significant inverse association between dairy consumption and anxiety; i.e., more dairy intake was associated with lower risk of anxiety [ 107 ]. Among the 17 cross-sectional studies of adult populations, 4 reported a statistically significant inverse association [ 5 , 13 , 110 , 111 ], 11 showed no association [ 6 , 7 , 14 , 16 , 57 , 60 , 106 , 112 115 ], and 2 noted mixed associations [ 12 , 104 ]. One study noted a statistically significant inverse association for women, but no association for men [ 12 ], while another study indicated a statistically significant inverse association for low-fat dairy intake and a positive association for high-fat dairy consumption [ 104 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is also possible that psychological problems might urge patients to restrict themselves. Several studies found that the pandemic increased people’s substance use due to social isolation and/or psychological problems [ 40 , 42 ]. Louvardi et al [ 43 ] indicated that patients with respiratory diseases worried more during the pandemic, and reduced substance use for fear of COVID-19 and related respiratory diseases and comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking (%) < 0.001* Current smoker 575 ( The negative associations of smoking and drinking with anxiety may be attributed to the released mental distress by the behaviors. However, previous studies indicated improving or worsening mental status due to substance abuse [39][40][41]. It is also possible that psychological problems might urge patients to restrict themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies reported negative dietary changes, especially an increase in meals and snacks. A possible explanation could be increased intake and consumption of high-caloric foods to cope with anxiety, sadness, and boredom during lockdown [ 14 , 15 , 46 49 ].…”
Section: Risk Factors and Unhealthy Behavior During The Covid-19 Pand...mentioning
confidence: 99%
“…Boaz et al reported women consumed sweet baked goods, vegetables, and olive oil more than men. On the other hand, men consumed red meat and sweetened/carbonated beverages more than women [ 46 ]. Most of the information about dietary changes was obtained from studies on the general population.…”
Section: Risk Factors and Unhealthy Behavior During The Covid-19 Pand...mentioning
confidence: 99%